ANALISIS PENERAPAN MANAJEMEN RISIKO TERHADAP KECELAKAAN KERJA DI SEKTOR MANUFAKTUR - Anisa Puspita; Dira Finanta; Cindy Rayani Ibrahim Sinulingga; Arsyadona (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze risk management and work accidents in the manufacturing sector. Risk management plays an important role in preventing work accidents, especially through the HIRARC (Hazard Identification, Risk Assessment and Risk Control) process. The manufacturing sector often faces various risks that can cause work accidents, such as mechanical, electrical and chemical hazards. This research uses a literature study method to identify factors that cause work accidents and implement effective risk control strategies. The research results show that comprehensive risk management can reduce work accidents significantly. Suggestions include improving employee training and implementing stricter safety procedures.